Ligand Binding Domain of Estrogen Receptor Alpha Preserve a Conserved Structural Architecture Similar to Bacterial Taxis Receptors - Lakshmanan Mangalath, Divya; Hassan Mohammed, Shabeer Ali (Frontiers in Ecology and Evolution, 2021)
It remains a mystery why Estrogen hormone receptors (ERs), which are highly specific towards its endogenous hormones, are responsive to chemically distinct exogenous agents. Does it indicate that ERs are environmentally regulated? Here we speculate that ERs would have some common structural features with prokaryotic taxis- receptor responsive towards environmental signals. This study addresses the low specificity and high responsiveness of ERs towards chemically distinct exogenous substances, from an evolutionary point of view. Here we compared the Ligand Binding domain (LBD) of ER alpha (α) with the LBDs of prokaryotic taxis receptors to check if LBDs share any structural similarity. Interestingly, a high degree of similarity in the domain structural fold architecture of ERα and, bacterial taxis receptors was observed. The pharmacophore modeling focused on ligand molecules of both receptors suggest that these ligands share common pharmacophore features. The molecular docking studies suggest that the natural ligands of bacterial chemotaxis receptors exhibit strong interaction with human ER as well. Though phylogenetic analysis proved these proteins are unrelated, they would have evolved independently suggesting a possibility of convergent molecular evolution. Nevertheless, a remarkable sequence divergence was seen between these proteins even when they shared common domain structural folds and common ligand-based pharmacophore features, suggesting that the protein architecture remains conserved within the structure for a specific function irrespective of sequence identity.